Peran Human Capital Dalam Meningkatkan Kinerja Perusahaan: Suatu Tinjauan Teoritis Dan Empiris - Endri (Business Administration Department - Universitas Katolik Parahyangan, 2010)
The present paper provides a review of the literature focusing the relationship betweenhuman capital and performance essentially at firm level. The exercise ofreviewing existing literature permitted to uncover three major neglected issues: 1)defining and measurement intellectual and human capital, 2) the analysis of humancapital - firm performance relationship; and 3) human resources management. Agrowing number of studies have attempted to show the link between human resourcesand firm performance.Keywords: human capital, human resources management, firm performance